Aneurysmal bone cyst: a rare surgical tumor of the rib - Kamdem, Marius; El Hammoumi, Massine; Amraoui, Mouad; Bhairis, Mohamed; Oukabli, Mohamed; Hassane Kabiri, El (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Bone cyst is a benign osteolytic cyst that develops within bone. There are mainly two types of bone cysts: the common form, simple bone cyst; and aneurysmal bone cyst (ABC), the uncommon form. The latter is rare and affects about one in a million people in a given year [1]. The most common location is on the long bone of legs, upper arms, spine, and pelvis [1]. The rib is an uncommon location of ABC. We report here two cases of ABC of the ribs.